The elfstones of Shannara - Brooks, Terry (New York : Ballantine Books, 1984)
The Ellcrys Tree is dying and upon its death hordes of demons will be released for a final epic battle. Wil Ohmsford and Amberle must carry an Ellcrys seed to the blood fire so a new Ellcrys will result and the demons will be banished.
"A Del Rey book.".
Sequel to: The Sword of Shannara.
Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: Elves -- Fiction; Good and evil -- Fiction; Shannara (Imaginary place) -- Fiction; Elves -- Fiction; Good and evil -- Fiction; Shannara (Imaginary place) -- Fiction; Fantastic fiction